A prospective Phase II study to examine the relationship between quality of life and adverse events of first‐line chemotherapy plus cetuximab in patients with KRAS wild‐type unresectable metastatic colorectal cancer: QUACK trial. (26th July 2018) - Iwamoto, Shigeyoshi; Ooki, Akira; Morita, Satoshi; Hara, Hiroki; Tanioka, Hiroaki; Satake, Hironaga; Kataoka, Masato; Kotaka, Masahito; Kagawa, Yoshinori; Nakamura, Masato; Shingai, Tatsushi; Ishikawa, Masashi; et al.
Abstract: A prospective trial has not been performed to investigate associations between quality of life (QOL), adverse events (AEs), and overall survival (OS) in the first‐line treatment with cetuximab plus standard chemotherapy for advanced/metastatic colorectal cancer (mCRC). Associations between patient outcome and health‐related QOL (HRQOL) together with skin toxicity‐related QOL were prospectively evaluated using EORTC QLQ‐C30 and DLQI questionnaires. One hundred and forty mCRC patients were analyzed in this study, and 87.8% received pre‐emptive skin treatment. Skin toxicity had no clinical impact on HRQOL or skin‐related QOL during the first 8 weeks and throughout the study period. An early skin reaction with a grade ≥2 at 8 weeks was significantly associated with a favorable OS compared with a grade of ≤1 (HR, 0.50; 95% CI, 0.24‐0.95; P  = .035) and was confirmed to be an independent predictor of OS (HR, 0.48; 95% CI, 0.21‐0.97; P  = .040). Patients symptomatic at baseline who responded to treatment had improved HRQOL compared to nonresponding patients. Severe mucositis/stomatitis had a statistically significant and clinically meaningful negative impact on HRQOL (mean changes from baseline throughout the study period in global health status were −12.64 for a grade of ≥2 vs −0.35 for a grade of 0 or 1 ( P  = .005)). In conclusion, severe early skin reactions predict favorable OS for patients treated with cetuximab plus chemotherapy without impairing QOL. In addition, mucositis/stomatitis was the most substantial AE compromising both QOL and treatment compliance. Abstract : This prospective study confirmed that severe early skin reactions predict favorable OS for patients treated with cetuximab plus chemotherapy without impairing QOL. Mucositis/stomatitis was identified as the most substantial adverse event compromising both QOL and treatment compliance.